3D modelling of the deposit profile in cold spray additive manufacturing. (July 2021) - Vanerio, Daniele; Kondas, Jan; Guagliano, Mario; Bagherifard, Sara
Abstract: New fields of application are coming along at an outstanding pace for cold spray deposition. More recently cold spray is being introduced as an additive manufacturing method that supersonically accelerates microparticles to induce bonding via severe plastic deformation. However, the thriving of cold spray as a widespread additive manufacturing technology with high production rates is still limited by inadequate geometrical control of the deposit shape. Thus, to establish cold spray in the additive manufacturing sector, substantial development is still required regarding digitalization and automatization of the process. To take a further step towards gaining control on the deposit geometry, present study reports the development of a 3D model able to simulate the cold spray deposit profile. The physical basis of the model is represented by a partial differential equation, which describes the deposit profile evolution as the number of passes grows. The model offers total freedom regarding the choice of the nozzle trajectory and the substrate geometry. The effects of the various process parameters, namely the number of scanning passes, spray angle, scanning speed and stand-off distance are implemented and realistically reflected in the model. More complex conditions like superimposed tracks with different spray angles, curved substrates, shadow effect and non-Gaussian profiles have been effectively simulated. The developed model has been validated with a wide range of experiments, demonstrating high accuracy and notable potential to promote the digitalization of cold spray additive manufacturing.